A qualitative study investigating the barriers to returning to work for breastfeeding mothers in Ireland. Issue 1 (December 2016) - Desmond, Deirdre; Meaney, Sarah
Abstract Background The World Health Organization (WHO) recommends that mothers exclusively breastfeed for the first 6 months of an infant's life. In Ireland, currently paid maternity leave is 26 weeks and the expectant mother is required by law to finish work 2 weeks before her expected delivery date. Mothers wishing to exclusively breastfeed for 6 months or longer find themselves having to take holiday leave or unpaid leave from work in order to meet the WHO's guidelines. The aim of this study is to explore women's experiences of breastfeeding after their return to work in Ireland. Methods This study was carried out utilizing a qualitative design. Initially 25 women who returned to the workforce while continuing to breastfeed were contacted, 16 women returned consent forms and were subsequently contacted to take part in an interview. Interviews were recorded and transcribed verbatim and thematic analysis was employed to establish recurring patterns and themes throughout the interviews. Results Women noted that cultural attitudes in Ireland coupled with inadequate or inconsistent advice from health professionals posed the biggest challenge they had to overcome in order to achieve to 6 months exclusive breastfeeding. The findings of this study illustrate that mothers with the desire to continue to breastfeed after their return to work did so with some difficulty. Many did not disclose to their employers that they were breastfeeding and did not make enquiries about being facilitated to continue to breastfeed after their return to the workplace. The perceived lack of support from their employers as well as embarrassment about their breastfeeding status meant many women concealed that they were breastfeeding after their return to the workplace. Conclusion While it has been suggested that WHO guidelines for exclusive breastfeeding for 6 months may be unattainable for many women due to work commitments, a different problem exists in Ireland. Mothers struggle to overcome cultural and societal obstacles coupled with inadequate support from health professionals. Encouraging and facilitating women to continue to breastfeed after they return to work will help to normalise breastfeeding within Irish culture and promote continued breastfeeding as a viable option for working mothers.